(3TPhQ GdPgH aj GdUfYI GdEdgjIs - (3Ydj Hf ehSi Hf Ydj, CHh GdMSf, GHf CQaY QCSg GdCfUGQj GdCfOdSj GdLjGfj,J (B593 (3g` s
(3ChdgG (B:s
(3bGd GdTjN GdGfUGQi bGajI GdCda GPG KdK GdeQjN HGdRgQI GeQD hbGQf HGdHOQ GdefjQ PcGA s
(3BNQgG (B:s
(3aGf cfJ ai Md GdQehR eOGfjG GNGfG abO fdJ GdPi cfJ QGLjG hGdG adGJQJY HgG agi QhVI bO GeJdCJ ddQGjOjf GdGaGYjG s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B26 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B249s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1029s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI WgQGf (B(1/1205) s
Keywords: (3GdcjejGA h GdWHjYjGJs